Species-specific effects of the invasive Hieracium pilosella in Magellanic steppe grasslands are driven by nitrogen cycle changes - Díaz Barradas, Mari Cruz (2015)
Aims: The principal objective was to evaluate the interference by the invasive species, H. pilosella, on native grassland species at the physiological performance level. We hypothesised that the invasive species is able to alter the nitrogen uptake of native plant species, and can modify community functioning. Methods: This study was performed under field conditions in the Magellanic Steppe (Argentina). We compared stable isotope signatures, nutrient content and several functional physiological traits in four grassland species with and without H. pilosella interference. Results: We found significant interference effects from the invasive species on native species, mostly through changes in nitrogen uptake. The variation in the natural abundance of foliar δ15N suggests that the native plants switched nitrogen sources due to interference with the exotic species. A linear relationship between chlorophyll and proline content that disappears when species are under H. pilosella interference, suggests major changes in the N allocation of native species. Grassland species under interference with exotic species exhibit lower photochemical efficiency and higher water use efficiency. Canonical discriminant analysis evidenced the existence of a different set of functional traits between invasive and native plants, and also among native species with and without H. pilosella interference. Conclusions: Our results support the hypothesis that H. pilosella exerts intense interference with native species through shifting the N sources available for native species, a lower leaf N content, and increasing water stress.